Analysis of Government Accounting Treatment in Land and Building Tax Revenue to the Bandung City Government - Romi Pudji Prayoga; Siti Kustinah (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the accounting treatment of Rural and Urban Land and Building Tax (PBB-P2) revenue and the effectiveness of realizing its revenue as part of Regional Original Revenue (PAD) in the Bandung City Government. The research uses a qualitative descriptive approach with data collection techniques through documentation studies and interviews at the Bandung City Regional Revenue Agency (Bapenda). The data analyzed included the target and realization of PBB-P2 revenues for the 2021–2024 period, the accounting recording system, and the mechanism for collecting and paying taxes. The results of the study show that the realization of PBB-P2 revenues has not consistently reached the set target, even though in some years it has been in the effective category. In terms of accounting, the treatment of PBB-P2 revenues has been carried out in accordance with accrual-based Government Accounting Standards (SAP), with recording carried out after cash is received in the Regional General Cash Account (RKUD) through the integrated systems of SIMPBB and SIPKD. In general, the management of PBB-P2 in the city of Bandung has shown efforts towards transparent and accountable regional financial governance, but it still requires strengthening the collection strategy and optimizing the system in a sustainable manner